A PHASE I EXPANSION STUDY OF PEGARGIMINASE, CISPLATIN AND PEMETREXED IN ARGININOSUCCINATE SYNTHETASE 1-NEGATIVE RECURRENT HIGH GRADE GLIOMAS (HGGS). (3rd October 2018) - Hall, Peter; Lewis, Rachel; Syed, Nelofer; Shaffer, Richard; Evanson, Jane; Ellis, Stephen; Williams, Matthew; Feng, Xiaoxing; Johnston, Amanda; Thomson, Jim; Harris, Fiona; Jena, Raj; et al.
Abstract: BACKGROUND: Patients (pts) with recurrent HGGs are usually managed with alkylating chemotherapy +/- bevacizumab. However, prognosis remains poor with an overall survival (OS) of 7–9 months. Preclinically, we showed that HGGs are a target for arginine depletion with Pegargiminase (ADI-PEG20) due to epimutations of argininosuccinate synthetase (ASS1) and argininosuccinate lyase (ASL). Moreover, ADI-PEG20 disrupts pyrimidine pools in ASS1-ve HGGs, thereby impacting sensitivity to the antifolate, pemetrexed. METHODS: We expanded a phase 1 trial of ADI-PEG20 with pemetrexed and cisplatin (ADIPEMCIS), which noted activity in aggressive thoracic cancers, to pts with relapsed HGGs (clinicaltrials.gov NCT02029690). Pts with ASS1-ve recurrent HGGs were enrolled (01/16 – 06/17) to receive ADI-PEG20 weekly at the maximum tolerated dose of 36 mg/m 2 i.m. plus PEM 500 mg/m 2 and CIS 75 mg/m 2 i.v. every 3 weeks for up to 6 cycles. Pts with disease control were allowed ADI-PEG20 maintenance. The primary endpoints were safety, tolerability and preliminary estimates of activity. Additional endpoints included pharmacodynamics, immunogenicity, OS, and ASS1/ASL epimutations. RESULTS: 10/19 ASS1-ve heavily pre-treated pts were enrolled onto ADIPEMCIS therapy. Treatment was well tolerated with the majority of adverse events (AEs) being CTCAE v4.03 grade 1–2; 7 pts (70%) had at least one grade 3 or 4 AE with neutropenia (40%) and thrombocytopenia (30%). The best response was stable disease by RECIST 1.1 and partial response (n=1; 10%) by RANO criteria. The median (95% CI) OS was 6.5 (1.8, 9.7) months. Two pts are alive and one continues 16 months on ADI-PEG20 as 3rd-line therapy for a de novo IDH-wildtype glioblastoma multiforme. Epimutations in ASS1 and/or ASL were detectable in pts' tumours consistent with prior studies. CONCLUSIONS: ADIPEMCIS was well tolerated and compares favourably to historical controls in recurrent HGG. A randomised, phase II trial comparing ADIPEMCIS with alkylating drugs at first relapse is planned (ATOMIC-G).